Sale and Purchase Contracts Through the Internet (E-Commerce) Judging From Civil Law, Electronic Transaction Information Law (ETIL) and Islamic Law - Risky Kurniawan Hidayat; Syahruddin Nawi; Sri Lestari Poernomo (Gerechtiheid Law Journal, 2020)
Abstract. Contracts or sale and purchase agreements that are regulated in the Civil Code and Islamic Law, while (e-commerce) is basically a modern trading transaction model regulated in Act Number 19 of 2016 amending Law Number 11 Year 2008 About Information and Electronic Transactions. The research aims to find out analyzing the validity of contracts for buying and selling via the Internet (e-commerce) in the Civil Law and Islamic Law (2) Similarities and differences in buying and selling contracts via the internet (e-commerce) according to the Civil law, the ETIL and Islamic Law. This research is included in the category of library research, namely research that analyzes books and produces a conclusion. The author makes a comparison of the results of the literature on contracts to buy and sell via the internet (e-commerce) in terms of the Civil Law and Islamic Law. Data sources consist of primary, secondary and tertiary legal materials for primary legal materials, namely the Civil Law and PERMA No. 2 of 2008 Sharia Economic Law Compilation, secondary legal materials include legal books and scientific journals and tertiary legal materials using legal dictionaries, and websites from the internet. The legal material from the results of the study was then analyzed by qualitative, qiyas (equalizing) and comparative analysis methods. The results of this study indicate that (1) The validity of e-commerce agreements in the Civil Law, is valid according to Article 1320 of the Civil Law and the principle of freedom of contract as stipulated in article 1338 of the Civil Law on freedom of contract. Whereas in Islamic Law, it is pronounced with a salam and istishna contract 'in article 20 of the Compilation of Sharia Economic Laws. So according to Islamic law it is also valid based on the salam agreement. (2) The similarity lies in the intent of the understanding of the sale and purchase agreement that together creates a legal relationship, the same concept of agreement, the equality of Article 1330 of the Civil Law and PERMA No. 2 of 2008 Article 4 Compilation of Sharia Economic Laws, equality of terms of the object of the sale-purchase agreement, equality of legal remedies against default parties. While the difference lies in a number of principles, differences due to the default law, and differences in dispute resolution.